The Aflibercept-Induced MicroRNA Profile in the Vitreous of Proliferative Diabetic Retinopathy Patients Detected by Next-Generation Sequencing - Guo, Ju; Zhou, Pengyi; Liu, Zhenhui; Dai, Fangfang; Pan, Meng; An, Guangqi; Han, Jinfeng; Du, Liping; Jin, Xuemin (Frontiers in Pharmacology, 2021)
Purpose: Vascular endothelial growth factor-A (VEGF-A) is an important pathogenic factor in proliferative diabetic retinopathy (PDR), and aflibercept (Eylea) is one of the widely used anti-VEGF agents. This study investigated the microRNA (miRNA) profiles in the vitreous of 5 idiopathic macular hole patients (non-diabetic controls), 5 untreated PDR patients (no-treatment group), and 5 PDR patients treated with intravitreal aflibercept injection (treatment group). Methods: Next-generation sequencing was performed to determine the miRNA profiles. Deregulated miRNAs were validated with quantitative real-time PCR (qRT-PCR) in another cohort. The mRNA profile data (GSE160310) of PDR patients were retrieved from the Gene Expression Omnibus (GEO) database. The function of differentially expressed miRNAs and mRNAs was annotated by bioinformatic analysis and literature study. Results: Twenty-nine miRNAs were significantly dysregulated in the three groups, of which 19,984 target mRNAs were predicted. Hsa-miR-3184-3p, hsa-miR-24-3p, and hsa-miR-197-3p were validated to be remarkably upregulated in no-treatment group versus controls, and significantly downregulated in treatment group versus no-treatment group. In the GSE160310 profile, 204 deregulated protein-coding mRNAs were identified, and finally 179 overlapped mRNAs between the 19,984 target mRNAs and 204 deregulated mRNAs were included for further analysis. Function analysis provided several roles of aflibercept-induced miRNAs, promoting the alternation of drug sensitivity or resistance-related mRNAs, and regulating critical mRNAs involved in angiogenesis and retinal fibrosis. Conclusion: Hsa-miR-3184-3p, hsa-miR-24-3p, and hsa-miR-197-3p were highly expressed in PDR patients, and intravitreal aflibercept injection could reverse this alteration. Intravitreal aflibercept injection may involve in regulating cell sensitivity or resistance to drug, angiogenesis, and retinal fibrosis.